2013
DOI: 10.1016/j.biomaterials.2012.11.055
|View full text |Cite
|
Sign up to set email alerts
|

The effect of microgrooved culture substrates on calcium cycling of cardiac myocytes derived from human induced pluripotent stem cells

Abstract: Induced pluripotent stem cell-derived cardiomyocytes (iPSC-CM) have been widely proposed as in vitro models of myocardial physiology and disease. A significant obstacle, however, is their immature phenotype. We hypothesised that Ca2+ cycling of iPSC-CM is influenced by culture conditions and can be manipulated to obtain a more mature cellular behaviour. To test this hypothesis we seeded iPSC-CM onto fibronectin coated microgrooved polydimethylsiloxane (PDMS) scaffolds fabricated using photolithography, or onto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
169
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(176 citation statements)
references
References 38 publications
6
169
1
Order By: Relevance
“…This particular pattern was adopted based on previous experiments with different pattern layouts, because it induced the greatest cellular alignment and nuclear elongation. 1 We plasma oxidized both groups under the same conditions, thus creating identical microtopography in both cases with grooves *0.5 mm deep. Films from both groups were deposited on top of glass coverslips, thus we consider that the films have roughly the same stiffness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This particular pattern was adopted based on previous experiments with different pattern layouts, because it induced the greatest cellular alignment and nuclear elongation. 1 We plasma oxidized both groups under the same conditions, thus creating identical microtopography in both cases with grooves *0.5 mm deep. Films from both groups were deposited on top of glass coverslips, thus we consider that the films have roughly the same stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Among different approaches, cell patterning induces the alignment and elongation of immature cardiac myocytes, improving many morphological and physiological properties of cardiac tissue, such as sarcomere organization, 1 Ca 2+ handling, [1][2][3] gap junction protein (connexin43) expression, 4 and directionality of action potential propagation. [5][6][7][8][9] Several different methodologies have been developed for cardiac tissue engineering using neonatal rat ventricular myocytes (NRVM) 2,[5][6][7][8][9] and induced pluripotent stem cellderived cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various other methods, such as microcontact printing, electrospinning, and microtopography, have previously been employed to control the structure of engineered cardiac tissue on the microscale [39][40][41] . While these techniques have proven successful in gaining cellular alignment, it is likely that the structure and function of in vivo cardiac tissue is governed by the much smaller, nanotopographical cues of the ECM and thus our NP substrate should prove advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that expression levels of genes of KCNH2, KCNE2 and KCNQ1 were higher in hiPSC-CMs than those in the human adult heart, whereas that of KCNE1 was similar between them (Uesugi et al, 2014). In addition, the extent of expression of a gene SLC8A1 encoding Na + / Ca 2+ exchanger 1 (NCX1) has been reported to be similar between adult heart tissue and structured hiPSC-CMs (Rao et al, 2013). Meanwhile, inward rectifier K + current (I K1 ) was shown to be hardly expressed in the hiP-SC-CMs (Ma et al, 2011;Doss et al, 2012;Meijer van Putten et al, 2015;Uesugi et al, 2014).…”
Section: The Field Potential Duration Of Hipsc-cms Sheetsmentioning
confidence: 99%